Systematics, genome mining, and biofuntionality of myxobacteria from rice straw - Gutierrez, Mary Victory Encarnacion (Animo Repository, 2024)
One of the most common agricultural wastes in the Philippines is rice straw, a residual byproduct from an economically important agricultural crop, the rice (Oryza sativa). This study aimed to investigate the occurrence and determine the diversity of myxobacteria in dried rice straws collected from two localities of Ilocos Sur, Philippines, and evaluate their metabolic and genotypic potential. The myxobacteria were isolated based on their fruiting body appearances on plant materials under moist incubation conditions. Morphology and molecular characterization based on 16S rRNA gene sequence revealed the diversity of the myxobacteria from rice straws. These bacterial isolates were affirmed by phylogenetic analysis to belong to the genera Chondromyces, Cystobacter, Stigmatella, Melittangium, and Myxococcus. Some of these myxobacterial isolates are potential new species of Cystobacter and Myxococcus based on their phylogenetic similarities to the nearest type strains. Screening of these isolates showed antimicrobial activities for the test bacterial and fungal isolates. Two draft genomes with two contigs for Cystobacter SBCy750 and one contig for Cystobacter SBCy751 which comprised 10,694,447 and 13,060,036 base pairs, respectively were studied. Notable parts of the genome mining of the Cystobacter SBCy750 and SBCy751 sequences are the biosynthetic gene clusters with postulated pharmaceutical properties. These included myxochelin iron chelator regulon as the product of nonribosomal peptide synthetase (NRPS), a hybrid NRP Polyketide cystomanamide A, B, C and D, ribosomally-synthesized post translationally modified peptides (RiPP) microviridin n9, n8, n7, n6, n5, n4 and n3. Some NRP type biosynthetic gene clusters with low gene similarity (<40%) were also annotated and these are predicted pathways for bioactive metabolites with therapeutics and cytotoxic properties like epothilones, heinamide, and kirromycin. Interestingly, there were also several unassigned BGCs encoding nonribosomal peptide synthetase (NRPS) , polyketide synthase (PKS) alkylpyrones, and ribosomally-synthesized post translationally modified peptides (RiPP) which could actually be responsible for production of specialized metabolites with pharmaceutical properties were also inscribed in the whole genome of SBCy750 and SBCy751. The results of the study show the diversity of myxobacteria from Philippine rice straws and their potential as sources of important molecules with biofunctional activities. KEYWORDS: Myxobacteria, Genome mining, Biosynthetic Gene Clusters (BGCs), Phylogeny, Systematics, NRPS, PKS, Microbial lysis